Serum lipid levels and lipoprotein subclasses in obese women residing in a rural area, Limpopo Province - Mampeule, Nakampe Stanley (My University, 2017)
Obesity has been associated with dyslipidaemia (increased levels of triglycerides, total cholesterol and low levels of HDL-C together with small dense lipoprotein particles) in the absence of metabolic disorders such as, type 2 diabetes mellitus and inflammation. Since community based studies in South Africa reported that obesity is more common in women, and rural Africans have a more favourable lipid profile compared to their White counterparts, the current study investigated the association of obesity in women without metabolic disorders with lipid levels and changes in proportions of small and large LDL and HDL particles. Methods The present study was part of the project “Prevention, Control and Integrated Management of Chronic Disease in a rural area, South Africa”. A total of 521 women participated in the above project. After excluding people with diabetes mellitus, insulin resistance and inflammation, 308 women were left and of these 67 were obese. Sixty seven ages matched, randomly selected non-obese women served as controls. Anthropometry variables as well as systolic and diastolic blood pressures were measured and the WHO steps questionnaire was administered to collect information on medication, lifestyle and diseases. Fasting blood levels of total cholesterol, HDL C, triglyceride, adiponectin, CRP, glucose and insulin were measured. Proportions of small and large HDL and LDL particles were determined. Results There was no significant difference in TC, TG and LDL-C levels (p=0.558, 0.087 and 0.948) between obese and non-obese women or between women with increased waist circumference (WC) and those with normal WC. The HDL-C concentration was significantly lower in obese women compared to women with non- obese (p=0.001). The lipid ratios TC/HDL-C and Apo B-100/Apo A-I were significantly higher in obese women than those with non- obese (p=0.013 and p=0.006) respectively. The same phenomenon was observed in women with xv increased waist circumference (p=0.001** and p=0.025* respectively). Adiponectin levels were significantly lower in obese women compared to non-obese women (p=0.004**) and in women with increased waist circumference compared to those with normal waist circumference (p=0.016*). The proportions of small dense HDL and LDL lipoprotein particles were similar in obese and non-obese women. Both obese and abdominally obese women had significantly higher odds ratios of low levels of HDL-C and elevated Apo B-100/Apo A-I. Adiponectin was a significant predictor of elevated TC and TG in both obese and abdominally obese women while BMI was a significant predictor of low HDL-C in obese women. Waist circumference was a significant predictor of low HDL-C in abdominally obese women. Conclusion In the current study, obesity in women was significantly associated with lipid abnormalities such as low HDL-C levels, raised lipid ratios (TC/HDL-C and Apo B 100/Apo A-I) and low levels of adiponectin, after excluding metabolic disorders
Thesis (MSc. Medical Science (Chemical Pathology)) -- University of Limpopo, 2017
Keywords: Obesity; Serum lipids; Lipoprotein subclasses; Adiponectin; Obesity; Obesity in women; Blood lipoproteins; Inflammation; Type 2 diabetes